2021
DOI: 10.1589/jpts.33.69
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to change and responsiveness of the Balance Evaluation Systems Test (BESTest), Mini-BESTest, and Brief-BESTest in patients with subacute cerebral infarction

Abstract: To compare the sensitivity to change and responsiveness of the Balance Evaluation Systems Test, Mini-Balance Evaluation Systems Test, and Brief-Balance Evaluation Systems Test in patients with subacute cerebral infarction. [Participants and Methods] Thirty patients with subacute cerebral infarction participated in this study. The Balance Evaluation Systems Test, Mini-Balance Evaluation Systems Test, Brief-Balance Evaluation Systems Test, Berg Balance Scale, and ambulatory ability were assessed on admission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
1
3
Order By: Relevance
“…These findings were similar to the results of a recent study that found an AUC of 0.82% at a cut-off score of 5.5 (sensitivity: 73%; specificity: 93%) determined by the ambulatory independence with or without an assisting device (external criterion); but the average duration between two assessments was longer as 78 days (more than 2 months). 24 The change score in the present study was higher than in previous studies that used the GRC as an external criterion. Godi et al 20 found the Mini-BESTest change score of 4 points and an AUC of >80% in mixed neurological diseases, while the study of Winairuk et al 24 found the Mini-BESTest change score of 3.5 with an AUC of >60% in cerebral infarction.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…These findings were similar to the results of a recent study that found an AUC of 0.82% at a cut-off score of 5.5 (sensitivity: 73%; specificity: 93%) determined by the ambulatory independence with or without an assisting device (external criterion); but the average duration between two assessments was longer as 78 days (more than 2 months). 24 The change score in the present study was higher than in previous studies that used the GRC as an external criterion. Godi et al 20 found the Mini-BESTest change score of 4 points and an AUC of >80% in mixed neurological diseases, while the study of Winairuk et al 24 found the Mini-BESTest change score of 3.5 with an AUC of >60% in cerebral infarction.…”
Section: Discussioncontrasting
confidence: 83%
“… 24 The change score in the present study was higher than in previous studies that used the GRC as an external criterion. Godi et al 20 found the Mini-BESTest change score of 4 points and an AUC of >80% in mixed neurological diseases, while the study of Winairuk et al 24 found the Mini-BESTest change score of 3.5 with an AUC of >60% in cerebral infarction. Moreover, using patient-rated and therapist-rated GRC scores were used as external criterion, the change score of the Mini-BESTest was ranged from 3.4 to 4 points and an AUC from 75% to 82% in Parkinson’s diseases.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations